The National Land Agency's Efforts in Anticipation and Resolving Disputes Regarding Multiple Land Ownership Certificates - Putri, Dwi Cinta Wiliananda; Hadi, Syamsul (Law Development Journal, 2025)
This study examines the role and efforts of the National Land Agency (BPN) in anticipating and resolving disputes over dual land ownership certificates in Indonesia. Dual certificates are a serious problem in land administration, creating legal uncertainty and potentially triggering social conflict. The research method used is normative juridical with a descriptive analytical approach, focusing on the study of land regulations such as the UUPA, PP No. 24 of 1997, and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/BPN. The results show that the BPN has implemented various preventive measures through an integrated land database system, the PTSL program, and electronic certificates (e-Certificates). In addition, dispute resolution is carried out through mediation, administrative clarification, and litigation at the State Administrative Court (PTUN). However, there is still a need to improve the integrity of the apparatus, procedural transparency, and strengthen the land information system to completely eliminate the practice of dual certificates and realize agrarian legal certainty in Indonesia.